Mapping Research Trends on Physics Learning Media Based on PJBL Model to Improve Critical Thinking Skills: A Review - Aris Doyan; Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti (Postgraduate, University of Mataram, 2025)
The Project-Based Learning (PjBL) model is a learning approach that emphasizes active student involvement through project-based activities. In the context of physics learning, the use of PjBL-based media has proven effective in encouraging students to think critically, as they are required not only to understand concepts but also to apply them to solve real-world problems. This research aims to identify and analyze research trends of physics learning media based on PjBL model to improve critical thinking. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. However, in 2024 there will be a decline in the research trend on it. There are many documents in the form of articles, proceedings, chapters, preprints, edited books and monograph that discuss research about physics learning media based pn PjBL model to improve critical thinking. Key words that are often used in research about it are collaboratin, communication, creativity, technology etc.